The Impact of heterogeneity in consumer characteristics on the design of optimal time-of-use tariffs - Murali,Karthik; Choi,Dong Gu (Energy, 2022)
Unlike commercial and industrial sectors where they have been successfully deployed, the rollout of voluntary Time-of-Use (TOU) tariffs in the residential sector has been tepid. One cause for this limited penetration of TOU tariffs in the residential sector is the difficulty in offering appropriate price incentives to a consumer class that is heterogeneous in its demographics and preferences. In this paper, we develop a parsimonious game-theoretic model to shed light on the optimal pricing problem from the utility's perspective when its consumers vary in their electricity consumption scheduling preferences as well as their willingness or flexibility to shift consumption in response to price incentives offered by the utility. Using this model, we generate structural insights into the role of the two types of consumer heterogeneity on the design and potential of voluntary TOU tariffs. We also show how our model and insights can be used to evaluate the current state and potential of TOU tariffs in two U.S. states.
Keywords: Supply Chain